GE_GERICHTE A/3035/2012 vom 31. Januar 2013 - GE Cour de justice (2013)
Non-lieu de saisie en continuation du séquestre; Plainte partiellement admise. | LP.91à109; LP.91.4; LP.93; LP.94.4; LP.99; LP.275